Abnormal mental phenomena in the prophets - Nussbaum, Kurt (Journal of religion and health, 1974)
Abnormal mental phenomena of varying emotional depth are found frequently among the earlier, nonliterary, and literary prophets. Three levels are discerned: inspiration, i.e., a state of excitement with well-preserved reality controls; ecestasy, as a state in which reality control has been lost temporarily; and eidetic imagery characterized by dreams and visions. It is argued that the prophets were psychotics, or mystics, or poets, or endowed with psychic gifts. I have attempted to consider some of these phenomena from the psychiatric viewpoint, keeping in mind that such interpretations many centuries later must remain speculative.